Alopecia universalis, hypothyroidism and pituitary hyperplasia: polyglandular autoimmune syndrome III in a patient in remission from treated Hodgkin lymphoma. (21st October 2010) - Quintyne, K I; Barratt, N; O'Donoghue, L; Wallis, F; Gupta, R K
Abstract : We herein report a case of a 33-year-old man in remission from Hodgkin lymphoma, who presented with reduced potency and hair loss. Initial endocrine tests revealed autoimmune hypothyroidism. An MRI of his pituitary gland at onset revealed hyperplasia. He tolerated replacement endocrine therapy with good response, but with no improvement in his alopecia universalis. A repeat MRI, 6 months after his initial endocrine manipulation, showed resolution of his pituitary hyperplasia.